Effect of Herbicides Doses and Dates of Application on Weed, and Weed Indices in Wheat - Acharya, Prabin; Bhattarai, Rajendra Kumar; Subedi, Roshan; Shrestha, Abishek (Journal of the Plant Protection Society, 2023)
Weeds pose a serious threat to wheat productivity. A study was undertaken during the winter season of 2019/20 in the experimental field, of the National Agronomy Research Centre, NARC, Khumaltar to assess various doses and application dates for controlling mixed weed flora in wheat. The experiment was laid out in a Randomized Complete Block Design with ten treatments replicated thrice with net a plot size of 6 sq. m. The treatments included metribuzin @ 250 g/ha at 25 DAS and 45 DAS, metribuzin @ 500 g/ha at 25 DAS and 45 DAS, carfentrazone @ 20 g/ha and @ 40 g/ha at 25 DAS, metribuzin+carfentrazone (@ 250 g/ha+ @ 20 g/ha) at 25 DAS, metribuzin+carfentrazone (@ 500 g/ha + @ 40 g/ha) at 45 DAS, pendimethalin @ 1000 g/ha at 2 DAS and weedy check. Data regarding the weed density and weed biomass were recorded following the standard procedures. The result revealed pendimethalin @ 1000 g/ha applied at 2 DAS, metribuzin @ 250 g/ha applied at 25 DAS, and metribuzin+carfentrazone (@ 250 g/ha + @ 20 g/ha) applied at 25 DAS, respectively, 24%, 33%, and 26% lower total weed density in comparison to the weedy check. The use of pendimethalin @ 1000 g/ha at 2 DAS showed the maximum herbicide efficiency index, 2.17%, closely followed by metribuzin @ 250 g/ha applied at 25 DAS (1.92%).